Sistem Pendukung Keputusan Menentukan Pemberian Pinjaman Modal dengan Metode Multi Attribute Utility Theory - Asyahri Hadi Nasyuha (STMIK Budi Darma, 2019)
Technology development is very rapid, computers are utilized not only limited to data processing but also as solutions to problem solving in various fields of science, one of which is a decision support system. Decision support systems have added value in helping decision making by utilizing data and models to solve unstructured problems. In this case the decision support system is used to determine business capital borrowing using the Multi Attibute Utility Theory method. From the research carried out, many people have proposed business capital loans so that the capital provider is difficult to determine the prospective acceptance of appropriate business capital. Multi Attribute Utility Theory is used to find weighted sums of performance ratings for each alternative based on the values of each criterion. Ranking is the result of calculations using the Multi Attribute Utility Theory method.